Acaricidal activity of plant extracts against Amblyomma variegatum in Waghimra, Northeastern Ethiopia - Teklu Yitbarek; Abebe Tibebu; Adane Bahiru; Ayalew Assefa (PLoS ONE, 2026)
Ticks are blood-feeding ectoparasites that cause significant economic losses by reducing animal productivity and damaging hides and skins. Ticks control and prevention strategies primarily rely on the regular use of synthetic acaricides. However, the widespread misuse of these commercial acaricides has led to the emergence of acaricide-resistant ticks, compromising their sustainable effectiveness. Therefore, this study aimed to evaluate alternative plant-based acaricides and determine their effective dose levels. Crude ethanol extracts from six plant species, previously reported to possess acaricidal activity, were initially screened at a concentration of 100 mg/mL using the adult immersion test. Based on the prescreening results, Ricinus communis , Azadirachta indica , and Jatropha curcas , which showed promising acaricidal effects, were subsequently tested at concentrations of 12.5, 25, 50, and 100 mg/mL. Tick mortality and oviposition inhibition were monitored over seven days at 3-hour intervals. Ricinus communis produced the highest acaricide efficacy (70 ± 1.8%) at 100 mg/mL. In comparison, 100 mg/mL of Azadirachta indica and Jatropha curcas resulted in 56.7 ± 2.2% and 16.7 ± 3.02% acaricide activity, respectively . The minimum lethal doses required to kill 50% (LD₅₀) and 90% (LD₉₀) of the tested ticks were 18.47 mg/ml and 184.3 mg/ml for Ricinus communis and 83.4 mg/ml and 431.8 mg/ml for Azadirachta indica , respectively. Ricinus communis exhibited the highest mean oviposition inhibition (98.5%), followed closely by Azadirachta indica (96.57%), while Jatropha curcas demonstrated comparatively lower inhibition (68.05%). A statistically significant dose-dependent oviposition inhibition effect was observed for Ricinus communis and Azadirachta indica (p < 0.05).In conclusion, Ricinus communis and Azadirachta indica demonstrated strong potential as botanical acaricide alternatives and warrant further evaluation in clinical trials.